Economic Valuation of Taman Wisata Air Wendit (TWAW) in Malang Regency: A Travel Cost Method - Shofwan Shofwan; Putri Haryati Sianturi; Eddy Suprapto (Journal of International Conference Proceedings (JICP), 2022)
As part of the results of utilizing the non-physical side such as natural beauty, fresh air, interesting experiences, and used water sources, nature tourism is an activity that is right to get the above benefits. The research problem is the value of Taman Wisata Air Wendit (TWAW) and the facilities that surround it and aims to analyze the implications of the economic value of TWAW on the welfare of the surrounding community. The travel cost method (TCM is expected to illustrate the surplus of benefits from consumer spending who enjoys TWAW. An individual's experience of being willing to pay to get the benefits of TWAW by variables consisting of distance, income, transportation costs and number of groups. From the estimation results, it can be found that the distance and income of visitors play a significant role in encouraging decision-making to visit TWAW. This has an impact on the high results of the economic valuation which is calculated to reach Rp. 158,081,234,97 per year. The findings also suggest that managers improve facilities and infrastructure to open the potential for additional volume of visits and have implications for increasing TWAW's economic valuation in the future.Keywords: Economic Valuation; Malang Regency; Taman Wisata Air Wendit (TWAW); Travel Cost Method